2007
DOI: 10.1007/s00424-006-0199-6
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensing across species

Abstract: The ability to detect changes in temperature is a fundamental sensory mechanism for every species and provides organisms with a detailed view of the environment. This review focuses on what is known of the neuronal and molecular substrates for thermosensation across species, focusing on the three robust model systems extensively used to study sensory signaling, the nematode Caenorhabditis elegans, the fruit fly Drosophila melanogaster, and the laboratory mouse. Nematodes migrate to thermal climes that are amen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 119 publications
(262 reference statements)
0
61
0
1
Order By: Relevance
“…In mice, TRPV3 and TRPV4 are both involved in thermotaxis response for selection of preferred warm temperatures whereas all three, TRPV1, TRPV3 and TRPV4, seem to have a role in avoidance of noxious hot temperatures (Dhaka et al, 2006). Various thermoTRP channels are also implicated in thermosensation and in thermotaxis behaviour of the nematode Caenorhabditis elegans and the fruit fly Drosophila melanogaster (Dhaka et al, 2006;McKemy, 2007;Dillon et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…In mice, TRPV3 and TRPV4 are both involved in thermotaxis response for selection of preferred warm temperatures whereas all three, TRPV1, TRPV3 and TRPV4, seem to have a role in avoidance of noxious hot temperatures (Dhaka et al, 2006). Various thermoTRP channels are also implicated in thermosensation and in thermotaxis behaviour of the nematode Caenorhabditis elegans and the fruit fly Drosophila melanogaster (Dhaka et al, 2006;McKemy, 2007;Dillon et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…The skin relays an array of thermal information critical for survival (McKemy, 2007). In humans, cold is perceived to be of greater intensity in glabrous skin than in hairy skin, with cold and pain thresholds occurring at warmer skin temperatures in the former (Harrison and Davis, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Despite in the past 13 years consistent evidence has been provided for the importance of TRPM8 as molecular mediator of cold sensations in a number of mammalian (209,210) and nonmammalian (114) animal models, it is not until recently that the expression of this channel on those specific first order thermo-sensory afferents, which have been repeatedly shown to respond to skin cooling and to convey temperature-dependent sensory inputs within the spino-thalamocortical tract in mammals, has been thoroughly characterized (85). Dhaka et al (85) have shown that in mice, TRPM8 appears to be expressed on a specific population of first order neurons, whose body are located in the dorsal root ganglion, and whose projections terminate in the skin at the level of the stratum spinosum and granulosum (i.e.…”
Section: Non-noxious Cold Transductionmentioning
confidence: 99%